2012
DOI: 10.1109/tns.2012.2212724
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Activated Oxyfluoride Glasses and Glass-Ceramics for Scintillation Applications

Abstract: Oxyfluoride glasses activated with Tb, Ce, Eu have been synthesized and studied. After heating at 580 and 750 crystalline phases were obtained. The samples were studied by DTA (Differential thermal analyzer), CL (cathodoluminescence), XRD (X-ray diffraction), SEM (scanning electron microscope), EDS (energy dispersive x-ray spectroscopy) methods. We found out that presence of crystalline phase enhances the CL of Tb activated samples significantly; whereas, the shortest decay time of 0.29 has been observed for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…As reported earlier, XRD studies of our samples indicated presence of LaF 3 and LiAlSiO 4 crystalline phases [11]. Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 84%
See 3 more Smart Citations
“…As reported earlier, XRD studies of our samples indicated presence of LaF 3 and LiAlSiO 4 crystalline phases [11]. Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 84%
“…Our previous studies showed luminescence intensity gain after heat treatment. We explained it with formation of LaF 3 crystallites [11].…”
Section: Scanning Electron Microscopymentioning
confidence: 92%
See 2 more Smart Citations
“…These materials have many applications -as infrared sensors to visualise the IR light using the up-conversion process [1], scintillators [2] and visible light phosphors. It is possible to compare various properties of oxyfluorides using not only different components but also glasses and glass ceramics with the same base components or varying the rare-earth activators.…”
Section: Introductionmentioning
confidence: 99%